La0.5Sm0.5FeO3: a new candidate for magneto-electric coupling at room temperature - Ranieri, M. G. A. (2017)
Samarium substituted lanthanum orthoferrite La0:5Sm0:5FeO3 thin film has been prepared by soft chemical method. A single perovskite phase with orthorhombic crystallographic structure was attained. Magnetic and ferroelectric orderings of the film is observed at room temperature (RT). The magnetization of the sample measured at room temperature increases non-linearly with the increase of magnetic field, which suggests the presence of dipole–dipole/exchange interaction in the sample. The resistivity measured in the temperature range 25–375 °C showed that the film is a semiconducting material with low resistivity. The Cole–Cole model reveals different grain boundaries electrical resistance caused by the equilibrium concentration of oxygen vacancies in orthoferrite and that the addition of samarium results in loss of oxygen during sintering. The ferroelectric behaviour of La0:5Sm0:5FeO3 at RT is also confirmed by its capacitance–voltage (C–V) characteristic suggesting a weak ferroelectric behaviour at room temperature. The variation of dielectric constant as a function of frequency predicts the presence of spontaneous polarization in the sample. The semiconductor electrical behavior of the La0:5Sm0:5FeO3 is mainly composed of tunneling current.